Stored product pests as models for trapping entomopathogenic fungi from olive tree orchards in Western Greece. (May 2020) - Mantzoukas, Spiridon; Pettas, Ioannis; Lagogiannis, Ioannis
Abstract: We used the following new range of insect species as baits for trapping entomopathogenic fungi: Plodia interpunctella, Rhyzopertha dominica, Tribolium confusum, Trogoderma granarium, Ephestia kuehniella and Tenebrio molitor, which constitute important stored product pests. Soil samples were collected from random points in olive tree orchards in Western Greece using Geographical Information Systems (GIS) and sample point coordinates were located with the Global Positioning System (GPS). Entomopathogenic fungi were identified by sequencing the ITS4 and ITS5 regions of the genomic DNA. Among the isolated fungal species, Beauveria bassiana and Metarhizium anisopliae showed the highest frequency, at 33.8% and 25.4% respectively. They also caused the most infestations of R. dominica and T. confusum whose mortality reached 33–97% and 87–100% respectively. We have also isolated various other fungal taxa such as Aspergillus alliaceus, Aspergillus insuetus, Aspergillus sp., Apophysomyces ossiformis, Chaetomium acropullum, Chaetomium sp., Chaetomium globosum, Chaetomium truncatulum, Trichoderma gamsii and Purpureocillium lilacinum . Our study confirms that T. confusum and R. dominica may be further utilized as baits for entomopathogenic fungi. Highlights: New range of insects used as baits for entomopathogenic fungi in soil samples. Beauveria bassiana and Metarhizium anisopliae most frequent among fungal isolates. Tribolium confusum and Rhyzopertha dominica showed highest mortality among insects. T. confusum and R. dominica promising as insect baits for entomopathogenic fungi.